PERANCANGAN VIDEO PROMOSI CAFE OMBEWOK - IBNU FAJAR, Dr. Nasrul Kamal, M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Cafe Ombewok established on 21 April 2016 the cafe is addressed at the Juanda no. 08 Padang, has the concept of Automotive with a diverse menu of native culinary mainstay Minangkabau like Iga Rendang, Ayam Sirah, and assorted drinks menu Cofee, Chocolate, Moctail, Squash and Tea. Cafe Ombewok have free wifi facilities, Live music, booking party and event Brithday. Lack of promotion done by the owner of Cafe Ombewok make this cafe is less known in the city of Padang. The author makes the design of audio-visual media in the form of a video, the video will be made into two versions, with a duration of 1 minute 26 seconds will uplod to youtube, facebook and twitter and the next version with a duration of 59 seconds will be uplod to social media instagram, with their promotional design is expected to make Cafe Ombewok known and able to compete with competitors-competitors.Keywords: promotions, videos, cafe, Cafe Ombewok